Use of double-balloon catheter in the management of epistaxis: A boon for the periphery - Bista, M; Baranwal, C; Maharjan, M; Kafle, P; Shresth, S; Toran, KC (Kathmandu University Medical Journal, 2010)
Background: Epistaxis is one of the most commonly encountered emergencies in ENT practise. It has been reported that almost 60% of general population experience epistaxis of small or large quantity in his /her lifetime1. Objective: The objective of this study was to compare the outcome of double ballon catheter to normal packing method for epistaxis. Materials and methods: An interventional study of 30 patients admitted in Kathmandu Medical College, Sinamangal, Kathmandu, Nepal from mid April 2008 to mid April 2009 with bleeding from the nose were taken into study. These patients were analysed on the basis of duration of hospital stay, any related cause for epistaxis, modalities of treatment, success of balloon catheter etc. Result: Results with double-balloon catheter showed less hospital stay and better compliance by the patient. Conclusion: This study highlights that double-balloon catheter has a higher chance of acceptance by the patient and is better in the treatment of epistaxis. This method can be undertaken without anaesthetic assistance thus it is very feasible even in the most remote areas of our nation. Key words: Epistaxis; Double-balloon catheter; Anterior nasal packing; Posterior nasal packing DOI: 10.3126/kumj.v8i2.3558 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 199-202